(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study determined the interactive learning strategies considered effective by business studies teachers for developing entrepreneurial skills among students in secondary schools in Anambra State. One research question was raised and two hull hypotheses were tested at 0.05 level of significance. The study adopted the descriptive survey design. The entire population of 192 business studies teachers in the existing 143 secondary schools in Awka, Nnewi and Onitsha Education zones of Anambra State were used for the study without sampling. A structured questionnaire that was validated by three experts was used for data collection. Cronbach’s alpha method was used to establish the reliability of the instrument which yielded a coefficient of 0.86. Mean and standard deviation were used to answer the research question and determine the homogeneity of responses, while t-test was used to test the hypotheses at 0.05 level of significance. The findings revealed that business studies teachers consider interactive learning strategieshighly effective for developing entrepreneurial skills among students in secondary schools in Anambra State. The findings also revealed that business studies teachers do not differ significantly in their mean ratings on interactive learning strategies considered effective for developing entrepreneurial skills among students in secondary schools in Anambra Stateas a result of their year of teaching experience and educational qualification. It was recommended among that interactive learning strategies should be frequently used by business studies teachers in the classroom.